THE STEPS TAKEN BY THE PROPHET MUHAMMAD TO BUILD ISLAMIC CIVILIZATION IN MEDINA ACCORDING TO THE BOOK OF AR-ROHIQUL MAKHTUM - Mohammad Izdiyan Muttaqin (Pondok Pesantren Modern Islam Assalaam, 2021)
Muslim Scholars continue to look for the best concepts to create Islamic Civilization. One of them is by studying the success story of the Prophet Muhammad SAW in creating Islamic civilization in Medina to be applied in modern society. This study aims to reveal the real steps taken by the Prophet Muhammad in Medina, which enable Muslims to develop a strong and influential civilization in the world. The author used the book Ar-Rohiqul Makhtum by Al-Mubarakfuri as the main reference. The author reached the conclusion that the Prophet Muhammad took several strategic steps in his da’wah in Medina, including: 1) Building a Mosque, 2) Brothering Muslims from the Muhajirin and Ansar, 3) Making a peace treaty with all of the Medina Citizens. The author agrees with Nabil As-Samaluti (2019) and Imam Amrusi Jailani (2016) that the concept of the State of Medina is a concept of peace for the entire citizens. This article also supports Komaruddin (2011), who stated that the Islamic State was not founded by coercion and violence.